Particle tracking velocimetry investigations on density dependent velocity vector profiles of a swirling fluidized bed - Naz, M.Y. (Taylor and Francis Inc., 2017)
Swirling fluidized bed (SFB) is a newer version of the well-known bubbling bed and very little know. An insight study is therefore required for complete understanding of the hydrodynamics of a SFB operation. The current study was conducted on stable regime of a SFB operated at different blade fin angles, blade inclination angles, particle densities and superficial air velocities. Roughly one quarter of the fluidized bed was photographed and its velocity vector field plots were generated using a MATLAB supported particle tracking velocimetry (PTV) technique. At lower superficial velocities, Gaussian distribution of the velocity vectors was predicted along the radius of the bed. Particles in the vicinity of the bed walls moved relatively slower than those marching in the middle of the bed. However, at higher superficial velocities, the particles closer to the cone boundary were moving with velocities comparable to the particles in the middle of the bed. Unlikely, the particles closer to the outer bed wall kept on moving with lower velocities regardless of increasing superficial air velocity. A further look into individual velocity vector profiles revealed negligible influence of smaller blade angles (9° and 12°) on particles’ motion. The overall velocity magnitude decreased by 6 with 3° increase in blade fin angle and by 9 with 5° increase in inclination angle. Contrarily, the particle velocity underwent a monotonic decrease with particle density. © 2017 Taylor & Francis.